2015
DOI: 10.1039/c4sc02383h
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of a small molecule receptor bound to dimethyllysine in lysozyme

Abstract: X-ray crystallography reveals how a calixarene can bind to dimethyllysine to form a complex with features similar to the aromatic cage motif of a chromodomain bound to a histone tail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 61 publications
(117 reference statements)
2
67
1
4
Order By: Relevance
“…A text-book example of such hybrid character is given by Vancomycin. 32 The potential of these hybrid receptors in the binding to specific single points of proteins is certainly attracting the interest of many chemists and biologists also because several are the examples of simple calixarenes able to bind single amino acids via inclusion of their lateral side chains in the cavity thanks to the combination of different interactions. It could be proved that, thanks to this binding ability, Vancomycin can block the cross-linking of this glycopeptide thus causing the cell wall lysis and inhibiting the growth of bacteria.…”
Section: Hybrid Charactermentioning
confidence: 99%
See 1 more Smart Citation
“…A text-book example of such hybrid character is given by Vancomycin. 32 The potential of these hybrid receptors in the binding to specific single points of proteins is certainly attracting the interest of many chemists and biologists also because several are the examples of simple calixarenes able to bind single amino acids via inclusion of their lateral side chains in the cavity thanks to the combination of different interactions. It could be proved that, thanks to this binding ability, Vancomycin can block the cross-linking of this glycopeptide thus causing the cell wall lysis and inhibiting the growth of bacteria.…”
Section: Hybrid Charactermentioning
confidence: 99%
“…53 Again, CH-π interactions and charge-charge salt bridges are simultaneously involved. 32 The sulfonated, cone shaped structure in fact well mimics the aromatic cage accompanied by carboxylate groups that several proteins, such as chromodomains, uses to recognize and complex di-and trimethylated lysines. Arg side chain results almost entirely submerged in the calixarene that buries ~230 Å 2 of the protein surface.…”
Section: Targeting Protein and Enzymesmentioning
confidence: 99%
“…3b) 32 and lysozyme. 33 In the former, binding occurred at three different sites, with the calixarenes acting as mediators of the PPIs required for crystallisation. 31 Please do not adjust margins Please do not adjust margins assays/sensors for antibody free detection of histone modifications through lysine side chain recognition.…”
Section: Calixarenesmentioning
confidence: 99%
“…We found that 8 was able to disrupt the CBX7-H3K27me3 interaction using a genetically encoded FRET biosensor, created by our collaborators in Robert Campbell's group. 43 Selectivity in the context of a folded protein arises from varying degrees of side chain accessibility, as well as different peripheral contacts between sulfonates and neighboring residues. 6).…”
Section: P-sulfonatocalix[4]arene Binds Post-translational Methylationsmentioning
confidence: 99%